Enhancing STEM Learning for All: A Paper Concept of Accessible Resources - Siregar, Nur Choiro; Gumilar, Aris; Warsito, Warsito; Amarullah, Ahmad; Rosli, Roslinda (Ibn Khaldun International Journal of Applied Sciences and Sustainability, 2023)
The accessibility of resources in science, technology, engineering, and mathematics (STEM) education is critical in ensuring equal opportunities for all students, regardless of their abilities or backgrounds. This paper presents a conceptual framework for enhancing STEM learning by implementing accessible resources. The concept explores the potential of educational materials, technologies, and teaching in promoting equitable access and improving learning outcomes in STEM subjects. The paper concept focuses on a comparative analysis approach to assess the impact of accessible resources on student achievement, engagement, and motivation in STEM. It proposes the collection of quantitative data to determine the effectiveness of various inclusive resources and identify any disparities in outcomes across diverse student populations. By considering the perspectives of multiple stakeholders, the paper concept aims to identify barriers to accessibility and propose to overcome them. It emphasizes the importance of understanding and addressing the unique needs of students, as well as the role of educators in practices. Furthermore, the concept highlights the significance of supportive policies and resource allocation to facilitate the integration of accessible resources in STEM education. The outcomes of this research concept will contribute to developing evidence-based practices that enhance STEM learning opportunities for all students. By emphasizing accessibility and providing guidance for educators, policymakers, and curriculum developers, this paper seeks to foster equitable learning environments in STEM education. Ultimately, it aims to empower all learners to actively participate and excel in STEM, promoting diversity and fueling innovation for a sustainable future.